Using Media in Religious Studies. Strategies of Representing Religion in Scholarly Approaches: Editorial Using Media in Religious Studies - Bärbel Beinhauer-Köhler (Journal for Religion, Film and Media, 2017)
Editorial of JRFM 2017, 3/2